Neuronal expression of CaMKⅡ and BDNF isoforms in mice with cognitive dysfunction induced by repetitive mild traumatic brain injury - LIU Dianqing; LIU Dianqing; LI Yun; LI Yun; ZHANG Jietao (陆军军医大学学报)
Objective‍　‍To investigate the calcium/calmodulin-dependent protein kinase Ⅱ （CaMKⅡ） signaling pathway and expression of brain-derived neurotrophic factor （BDNF） isoforms in mouse model of cognitive dysfunction secondary to repetitive mild traumatic brain injury （rmTBI）. Methods‍　‍A total of 63 male C57BL/6J mice （5 weeksd old， werghing 16~17 g） were divided into model group （n=50） and control group （n=13）. The mice of the model group received modified weight drop and repeated head impacts to establish a model of rmTBI， and the mice from the control group were only given anesthetic treatment. From the 30th day after the end of modeling， Morris water maze test was applied to evaluate the spatial learning and memory abilities， and the relative data was evaluate for correlation analysis. According to the taxonomy of cognitive levels， the model group was further stratified into high-， medium- and low-performance groups. After the mice with medium-performance group were eliminated， and the indicators of water maze test were compared among the high-performance， low-performance， and control groups. After the behavioral experiment， Western blotting was conducted to detect the expression of CaMKII， α-amino-3-hydroxy-5-methyl-4-isoxazole-propionicacid receptor （AMPAR） subunits （GluR1， p-GluR1， GluR2）， and different isoforms of BDNF （mBDNF， proBDNF） in the prefrontal cortex and hippocampus. The expression levels were compared among the groups. Results‍　‍① There were significant correlations among the water maze-related indicators（P<0.05）. The mice in the model group were divided into 3 groups of high- （n=31）， medium- （n=11） and low-performance （n=8） levels through hierarchical clustering， and there were differences in cognitive levels in the high-performance， low-performance and control groups. ② The phosphorylation level of GluR1 in the hippocampus was significantly decreased in the high-performance group than the control group and the low-performance group （P<0.05）. When compared with the control group， the expression of GluR1 and GluR2 in the prefrontal cortex of the low-performance group was increased （P<0.05）， and the expression of GluR2 and CaMKⅡ in the prefrontal cortex of the high-performance group was increased （P<0.05）. The low-performance group obtained obviously lower GluR1/GluR2 ratio than the high-performance group （P<0.05）. ③ When compared with the control group， the low-performance group exhibited notably elevated expression of proBDNF and mBDNF （P<0.05） and mBDNF/proBDNF （P<0.05） in the prefrontal cortex and hippocampus， while the high-performance group had enhanced expression of mBDNF in the prefrontal cortex （P<0.05）. Conclusion‍　‍In the chronic phase of rmTBI， prognosis of good cognitive function is accompanied by up-regulation of CaMKⅡ signaling pathway， and the difference in cognitive function is accompanied by the change in proportions of different AMPAR subunits on the postsynaptic membrane. In the cognitive impairment group， there is an overexpression of 2 types of BDNF isoforms and an increase in the conversion rate of mBDNF.